Effect of Reflexology on the Side Effects of Chemotherapy in Cancer Patients: An Integrative Review - Hesam Gholamzadeh; Mahnaz Ilkhani; Ahmad Ameri; Nezhat Shakeri (Mashhad University of Medical Sciences, 2019)
Background: The global cancer incidence and the number of survivors are increasing. Therefore, it is necessary to pay more attention to the side effects of treatment. Aim: The aim of this study was to assess the effect of reflexology on the side effects of chemotherapy in cancer patients. Method: For finding the related articles, the researchers searched several databases including PubMed & ProQuest and valid websites including ScienceDirect, Google Scholar, Scientific Information Database, and Magiran. The key terms of "reflexology, cancer, and chemotherapy" individually and combined together were searched in Parisian and English, and the studies performed from 2009 to 2018 were extracted. Due to the lack of sufficient studies carried out into the outcome of reflexology on chemotherapy, both Persian and English articles were used. Results: A total of 57 studies were extracted from the databases and valid websites; five of which met the inclusion criteria. All selected studies were clinical trials. Implications for Practice: Reflexology can be used as a non-pharmacologic nursing intervention to alleviate the side effects of chemotherapy and improve the quality of life of cancer patients.